Lgbts and gender banned? Genealogical notes about law projects in Brazil - Galindo, Dolores; Cazeiro, Felipe; Serra, Arthur Galvão; De Souza, Leonardo Lemos [UNESP] (Universidade Estadual de Maringa, 2017)
This research propose analyze, with a genealogic perspective, the effects of a cis-heteronormativity dispositive of sexuality that in their attempts to control bodies and molds lives - through nationalist programmatic technologies, moralizing, familists - articulates pathologizing, criminalization and extermination. This dispositive, in the 2015/2016 coup, propagated hated against people fleeing the conservative standards. For this, we started methodologically from a genealogy about the discourses produced by legal standards in process and/or established in Brazil who claim the ontology of a true sex and silence divergent positions. It is a psychology as subjectivities production technology that silences, but also resists normalizing demands and refusing to produce a moral grammar and weaken participatory democracy. Even with these considerations, his agenda today lies in defense of secular work on behalf of differences in gender and sexuality that produce new differences, rather than regular identitarity and submissions that undermine the place of politics.
Keywords: Gender; Human rights; Psychology